2018
DOI: 10.1016/j.clinbiomech.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

A new methodology based on functional principal component analysis to study postural stability post-stroke

Abstract: The proposed methodology allows Functional Principal Component Analysis to be performed when data is scarce. Moreover, it allowed the dynamics of recovery of two different treatment groups to be determined, showing that the techniques added in the target group increased postural stability compared to the base protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…Additionally, this study employed time-series principal component analysis and observed significant differences in the fourth principal component of the rectus femoris muscle. Action recognition scoring and research related to time-series principal component analysis have gradually matured (Xiaolin Liu er ai., 2023) and have been widely applied in studies such as movement development, movement technique analysis (Huijie et al, 2012), sports injury diagnosis (Donoghue et al, 2008;Epifanio et al, 2008), and rehabilitation outcome assessment (Sánchez-Sánchez et al, 2018). This study identified the fourth principal component of the rectus femoris muscle as a sensitive indicator for action recognition.…”
Section: Trapezius Muscle Key Force Phase Recognitionmentioning
confidence: 95%
“…Additionally, this study employed time-series principal component analysis and observed significant differences in the fourth principal component of the rectus femoris muscle. Action recognition scoring and research related to time-series principal component analysis have gradually matured (Xiaolin Liu er ai., 2023) and have been widely applied in studies such as movement development, movement technique analysis (Huijie et al, 2012), sports injury diagnosis (Donoghue et al, 2008;Epifanio et al, 2008), and rehabilitation outcome assessment (Sánchez-Sánchez et al, 2018). This study identified the fourth principal component of the rectus femoris muscle as a sensitive indicator for action recognition.…”
Section: Trapezius Muscle Key Force Phase Recognitionmentioning
confidence: 95%
“…Connected with the current trend of increasing age of the population [ 2 , 3 ], this has led to a rise in pathologies that affect balance, causing an increased risk of falls in the elderly population. Around 30% of people aged over 65 years, and more than 50% of individuals in health centers or care homes suffer one or more falls per year, and between approximately 20% and 30% of the global population has had or will have a vertiginous episode in their lives [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the applications of functional data analysis techniques have been successfully implemented in many different fields during the last years, for examples, environment and ecology (Gao and Niemeie 2008;Ikeda et al 2008;Torres et al 2010;Sierra et al 2017;Dennis et al 2019), hydrology and metrology (Berrendero et al 2011;Suhaila et al 2011;Chebana et al 2012;Suhaila and Yusop 2016;Beyaztas and Yaseen 2019;Hael et al 2020), in economics and finance (Müller et al 2011;Feng and Qian 2018), demography (Hyndman and Booth 2008;Hyndman and Shang 2010;Han et al 2018), and science and biomedicine (Illian et al 2009;Sánchez-Sánchez et al 2018;Granato et al 2018;Reiss and Xu 2019). For more details, (Ullah and Finch 2013) prepared a systematic review to identify FDA application studies in many different areas.…”
Section: Introductionmentioning
confidence: 99%